DIAGENESIS RESERVOIR BATUAN KARBONAT DI LAPANGAN ALUR SIWAH CEKUNGAN SUMATERA UTARA, ACEH TIMUR - Adhitiawan, Erham
Alur Siwah Field is one of biggest gas field in Block “A” which is operated by PT Medco E&P Indonesia. It is located in Aceh Timur, Nanggroe Aceh Darussalam Province, approximately 12 kms south of Bindjai City. Alur Siwah is located in North Sumatra Basin and the gas reservoir is produced by carbonates from Peutu and Tampur Formations. Since it discovered in 1972 by Asamera, not less than 10 wells has been drilled and 7 of them were delineation wells to produce gas from that carbonate formations. However, the delineation wells have revealed significant different in test results and suspect it is because of heterogenity in porosity and permeability distributions in that reservoir. One of major factor that control heterogenity is diagenetic process that it will explain further in this study. The main purpose of this study is knowing the processes which causes and controlled the difference porosity and permeability in each well in Alur Siwah with diagenetic analysis approach. The metode that been used is using analysis in seismic, core, cutting, thin section and well logs data. Petrophysics analysis and geomodelling is used as a secondary data. Base on analysis and interpretation from all cores, cuttings and its thin sections, reservoir in Alur Siwah is dominated by muddy carbonate facies with minor patch reef facies which unconformably deposited above Tampur dolostone. Depositional environment of the reservoir is lagoonal system and its diagenetic setting is in vadose, freshwater phreatic and mixing zone. The step of diagenetic process in Alur Siwah’s cabonate is erosional porosity until late burial diagenesis. However from that process, fracturing contributions will increase gas rate production from the poor porosity reservoir.